Mini-course Braumann II EMMBM - Braumann, Carlos A. (2008)
Scientific meeting: II Encontro em Modelagem Matemática em Bio-Medicina, Campinas, Brazil, Feb 1-2, 2007. Invited pre-meeting (Jan 30-31, 2007) mini-course on stochastic differential equations.